The triumph of truth - Hulett, Marcia Ione (My University, 1893)
Introduction: The past century has been one great interrogation point. Never before has the spirit of inquiry so possessed the people as at present. Yet the questions which today are most seriously troubling the minds of some of the best thinkers of the world, are questions which have agitated scientific men from the beginning—the questions relating to man’s own origin, his present life, and his future destiny. What must the first man hand woman have thought of this life as they looked about them, when turned out of the Garden of Eden when they saw the fiery king of day, rising in a sea of glory and pursuing his burning course through the blue _____ of heaven, only to sink to rest, leaving the brightness of his track to fade gradually from their wondering sight—what unanswerable questions must they have asked themselves when they gazed into the midnight sky and saw the pale Queen of Night with all her troop of stars, giving their soft and silvery light to the darkened world.
Citation: Hulett, Marcia Ione. The triumph of truth. Senior thesis, Kansas State Agricultural College, 1893.
Morse Department of Special Collections
Keywords: Truth; Theses; Manuscripts (documents)